Bank Competition and Financial Stability : A General Equilibrium Exposition - Lucchetta, Marcella (IMF Working Papers; Working Paper, 2011)
We study versions of a general equilibrium banking model with moral hazard under either constant or increasing returns to scale of the intermediation technology used by banks to screen and/or monitor borrowers. If the intermediation technology exhibits increasing returns to scale, or it is relatively efficient, then perfect competition is optimal and supports the lowest feasible level of bank risk. Conversely, if the intermediation technology exhibits constant returns to scale, or is relatively inefficient, then imperfect competition and intermediate levels of bank risks are optimal. These results are empirically relevant and carry significant implications for financial policy.